Multicenter review of liver transplant for hepatitis B‐related liver disease: disparities in gender and ethnicity. (3rd September 2013) - Campsen, Jeffrey; Zimmerman, Michael; Trotter, James; Hong, Johnny; Freise, Chris; Brown, Robert S.; Cameron, Andrew; Ghobrial, Mark; Kam, Igal; Busuttil, Ronald; Saab, Sammy; Holt, Curtis; et al.
Abstract Orthotopic liver transplantation (OLT) is the preferred treatment for selected patients with hepatitis B virus (HBV)‐related liver disease. This study aimed to (i) define long‐term outcomes following OLT for HBV; (ii) to quantify the incidence of HBV recurrence (rHBV) as it relates to anti‐HBV treatment; and (iii) to determine outcomes for specific patient subgroups. We performed a retrospective chart review of 738 patients undergoing OLT between 1985 and 2010 at seven US transplant centers and divided the patients into 3 eras, 1985–1994, 1995–2004, and 2005–2010, based on hepatitis B immunoglobulin and antiviral therapies. In Era 3, female gender (p = 0.002), recurrent hepatocellular cancer (p < 0.001), and retransplantation (p = 0.01) were significantly associated with worse survival on multivariate analysis. Survival at three yr was poor for all ethnicities in Era 1, but significantly improved for all except black Americans by Era 3. Era 2 data showed a continued increase in rHBV from five to 10 yr (16.6%, 26.2%). In conclusion, while OLT outcomes have improved because of combination antiviral and immunoglobulin therapy, women and black Americans may not have realized an equal benefit. The rate of rHBV is significant even 10 yr post‐transplant with survival affected.